The strategy of tourism village development in the hinterland Mount Bromo, East Java - Siti Mujanah; Tri Ratnawati; Sri Andayani (Universitas Hayam Wuruk Perbanas, 2015)
This study aims to find an effective strategy in the development of Hinterland Tourism Village in Mount Bromo area. It is a descriptive explanatory research to build a model of grand design for rural tourism development. It took three tourism villages around Bromo Mountain and the data were collected by survey or interviews on both local and interna-tional tourists and by cross checking among the interviews on rural principles for the data validity and reliability. The data were analyzed using SWOT analysis to determine the strategy and Analytical Hierarchy Process (AHP) to determine the ranking of objects and tourist attractions/obyek dan daya tarik wisata (ODTW). The results of SWOT analysis was based on the weight and value scores of respondents indicating that the development of rural tourism was scored in the first quadrant for a strategy to optimize the strengths and opportunities. It shows that the AHP Wonokitri village has the highest number, the second is Ngadisari, and third village is Ngadas. The model of strategy of rural tourism can be developed when the program are supported optimally by the com-munity and the government such as the Center Government for Taman Nasional Bromo, Tengger, Semeru (TNBTS), Department of Tourism, Public Works (PU), Cooperation, and Society Empowerment Department, while also support by private sectors, SMEs and local investors and also education institutions.